Cross-border mergers and acquisitions of Chinese firms: an investigation of value creation - Tu, Wenjun (2017)
The surge of cross-border mergers and acquisitions (CBM&As) from China, the largest of the emerging economies, has attracted considerable scholarly attention recently. The unique institutional context in China, i.e., heavy government involvement in business activities and imbalanced development of subnational institutions among Chinese regions, raises two interesting questions: whether, or not, CBM&As of Chinese firms create value for acquirers in the short and the long term; and what special sources of value creation exist in Chinese firms’ CBM&A? The main focus of this thesis is to investigate the impact of multi-level institutional variables on short- and long-term value creation in Chinese firms’ CBM&A in the unique Chinese context. Using a sample of 279/192 CBM&A events collected from the CSMAR database over the period 1999-2013, we find that the market reacts positively to CBM&A announcements, but the accounting performance of acquirers fails to improve after CBM&A in the long term. Based on the selected sample, we employ Ordinary Least Squares to analyse the data and find the following results. First, the study reveals government is an important source of value creation, but its effects on the short- and long-term value creation in Chinese firms’ CBM&A are reflected by government ownership and political connections. We find Chinese market investors reward acquirers with political connections at the time of CBM&A announcements, but explicit government ownership contributes more to long-term performance improvement of acquirers after CBM&A. Second, in the long term, we find there is U-shaped relationship between R&D intensity and the long-term post-CBM&A performance of acquirers, which suggests acquirers with moderate-level R&D intensity suffer from more integration problems resulting from the dilemma of compatibility. Third, at the macro level, we find that higher-quality institutions among the Chinese regions and higher-quality host country institutions provoke more positive market reactions, while less cultural distance and greater formal institutional distance contribute to performance improvement of acquirers after CBM&A in the long term. Furthermore, the effects of micro-level institutional factors, i.e., government ownership and political connections, on the value creation in Chinese firms’ CBM&A are dependent on the macro-level institutional environments. In the short term, the market responds more positively to acquirers with higher government ownership, but less positively to acquirers with political connections with an increase in subnational institutional quality. With the increase in host country institutional quality, the market responds less positively to both the larger government ownership and the presence of political connections. In the long term, we find that the influence of government ownership on value creation is enhanced with the increase of cultural distance, but declines with the increase of formal institutional distance.